Memory Retrieval-Extinction Combined With Virtual Reality Reducing Drug Craving for Methamphetamine: Study Protocol for a Randomized Controlled Trial - Liu, Wang; Chen, Xi-Jing; Wen, Ya-Tong; Winkler, Markus H.; Paul, Pauli; He, Yi-Ling; Wang, Liang; Chen, Hong-Xian; Li, Yong-Hui (Frontiers in Psychiatry, 2020)
Background: Relapse, often precipitated by drug-associated cues that evoke craving, is a key problem in the treatment of methamphetamine use disorder (MUD). Drug-associated memories play a major role in the maintenance of relapse. Extinction training is a basic method for decreasing drug craving by suppressing drug-associated memories. However, the effects are often not permanent, which is evident in form of spontaneous recovery or renewal of cue-elicited responses. Based on memory reconsolidation theory, the retrieval-extinction (R-E) paradigm may be more effective in decreasing spontaneous recovery or renewal responses than extinction. After the original memory reactivated to a labile state, extinction will be introduced within the reconsolidation window, thereby updating drug-associated memories. However, there are still some controversial results, which suggest that the reactivation of drug-associated memories and the 10min-6h of limited time window are two main elements in the R-E protocol. Virtual reality (VR) is supposed to promote memory reactivation by providing vivid drug-related stimuli when compared with movies. Objective: The aim of this study is to examine the effectiveness of R-E training combined with VR on reducing spontaneous recovery or renewal of cue-elicited responses, in comparison to extinction, R-E training provided outside the time window of 6hrs and R-E training retrieved using videos, in methamphetamine abusers. Methods: The study is a parallel matched controlled study including 220 participants with MUD. Participants will be randomly assigned to either a R-10min-E group (methamphetamine-related cues retrieval in VR followed by extinction after 10mins) or a NR-10min-E group (neutral cues retrieval in VR followed by extinction after 10mins) or a R-6h-E group (methamphetamine-related cues retrieval of VR followed by extinction after 6hrs) or a RV-10min-E group (methamphetamine-related cues retrieval in videos followed by extinction after 10mins). Cue-evoked craving and reactivity will be assessed at pre-test and at 1-day, 1-week, 1-month, and 6-month post-tests. Discussion: To our knowledge, this study will probably be the first study to examine the efficacy of R-E training combined with VR to reduce cue-evoked responses in people with MUD. This innovative non-pharmacological intervention targeting drug-associated memories may provide significant clinical implications for reducing relapse, providing the study confirms its efficacy.